Zwischen Exportabhängigkeit und Binnenmarkterschließung: Brasilien in der Schuldenfalle - Sangmeister, Hartmut (Vierteljahresberichte / Friedrich-Ebert-Stiftung, 1988)
Brazil's range of exports includes increasing numbers of industrial products. Still being dependent on foreign patents and technology, Brazil is forced to make restrictions in this area due to the shortage of foreign currency. The growing integration of the Brazilian economic system has benefited its modernization. Nevertheless, figures currently available indicate that the Brazilian economy's real per capita income is falling while inflation rates are rising again
Keywords: Brasilien